Mergers and acquisitions in Brazil and economic uncertainty shocks - Alexandre Teixeira Norberto Batista; Wagner Moura Lamounier; Poueri do Carmo Mário; Bruno Pérez Ferreira (Contextus, 2022)
In this paper, we have analyzed the sensitivity of the aggregate volume of Mergers and Acquisitions (M&A) in Brazil to fluctuations (shocks) in the Economic Uncertainty level from 2010 to 2021 under behavioral and neoclassical theoretical foundations on the M&A causes. We estimated a Vector Autoregressive (VAR) model with the volume of M&A announcements, the Brazil Economic Uncertainty Index (IIE-Br), and macroeconomic and market variables. There is evidence that the M&A announcements in Brazil can respond positively to an economic uncertainty shock. Thus, we contribute with empirical evidence to understand the role of macroeconomic factors, including economic uncertainty, in the future conduct of the M&A market.